2019
DOI: 10.21203/rs.2.17088/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chronic patients’ satisfaction and priorities regarding medical care, information and services and quality of life: a French online patient community survey

Abstract: Background: The French healthcare system is evolving to meet the challenges of an aging population, the growing prevalence of chronic diseases, the development of new technologies and the increasing involvement of patients in the management of their disease. The aim of this study is to assess the satisfaction and priorities of chronic patients regarding medical care, information and services and their quality of life. Methods: A cross-sectional study was conducted from February to March 2018 via the French Car… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
(10 reference statements)
0
3
0
1
Order By: Relevance
“…Evidence demonstrated that type 2 diabetes is potentially reversible [28,29] by early diagnosis and higher patient participation in disease management [30]. Accordingly, health policy must deal with the implementation of diabetes management regimens more tailored to individual patient's treatment-effectmodifiers [31] and aimed at increasing their awareness and satisfaction [32]. Traditional therapies revealed to entail increased costs in the long-term due to the need for treatment intensification after around 8 years and the increased requirement of medication and outpatient visits caused by non-fatal events [9].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence demonstrated that type 2 diabetes is potentially reversible [28,29] by early diagnosis and higher patient participation in disease management [30]. Accordingly, health policy must deal with the implementation of diabetes management regimens more tailored to individual patient's treatment-effectmodifiers [31] and aimed at increasing their awareness and satisfaction [32]. Traditional therapies revealed to entail increased costs in the long-term due to the need for treatment intensification after around 8 years and the increased requirement of medication and outpatient visits caused by non-fatal events [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, having a high UHC index value does not imply that high-quality care is provided for each specific disease. For example in countries with high UHC index value (87), quality medical care services were found to be inadequate for patients with chronic diseases (88). Quality of health care can also be assessed using structure, process, and outcome indicators in the healthcare system (89).Therefore, generally, measuring the quality of care for specific diseases is helpful for stakeholders, clinicians, and health policymakers working on specific health problems (90).…”
Section: Discussionmentioning
confidence: 99%
“…De tevredenheid over de afstemming tussen zorgverleners is in 2020 niet anders dan in eerdere jaren. Al sinds enige jaren blijkt uit zowel nationaal als internationaal onderzoek dat een grote groep patiënten ontevreden is over de afstemming tussen zorgverleners en de toegang tot multidisciplinaire zorg [3,20,21]. Een op de vier mensen met een chronische ziekte geeft bijvoorbeeld aan dat zorgverleners zeer beperkt met elkaar overleggen over hun zorg [3].…”
Section: Beschouwing En Conclusieunclassified